Valuation of Microsoft Corporation : An Analysis of Financial Performance and Future Growth Prospects - Pipek, Jan (2024)
This thesis conducts a comprehensive valuation of Microsoft Corporation, examining its financial performance and future growth prospects in the context of the transformative impacts of artificial intelligence and cloud computing. The study aims to develop a rigorous valuation model for Microsoft and its principal segments (Productivity and Business Processes, Intelligent Cloud, and More Personal Computing) to identify key value drivers and assess alignment with market valuation. The methodology employs a two-phase Discounted Cash Flow (DCF) analysis for Microsoft and its segments, complemented by Sum-of-the-Parts (SOTP) assessment. Peer group analysis and parametric calculation are used for estimating betas, while revenue-based modelling addresses uncertain variables in the Free Cash Flow to Firm (FCFF) equation. The results indicate that Microsoft's market capitalization as of September 2024 is $3.2 trillion, suggesting a 34% deviation from its $2.4 trillion intrinsic valuation. The Intelligent Cloud segment emerges as the primary growth driver, with substantial capital expenditure requirements. Sensitivity analyses reveal Microsoft's vulnerability to growth assumptions. The study concludes that while Microsoft exhibits strong fundamentals, its market valuation incorporates optimistic growth expectations, particularly concerning the pace of AI and cloud adoption. The findings underscore the importance of assessing market expectations critically and highlight the pivotal role of strategic investments in AI and cloud computing for Microsoft's future value creation.